Application of Laser Scanning to Assess the Roughness of the Diaphragm Wall for the Estimation of Earth Pressure - Marek Wyjadłowski (MDPI AG, 2021)
The correct estimation of earth pressure is important for the design of earth retaining structures and depends, among others, on the surface morphology of retaining structures. The diaphragm wall created as a protection of a deep excavation located in an urbanized area was selected as a research object. Terrestrial Laser Scanning (TLS) was used for the investigation of the unique surface (in real-world dimension) obtained by tremieying the concrete in different soil layers. An original and innovative procedure for concrete surface description was developed, which includes steps from the TLS measurement to the determination of the roughness parameters. The tested samples from anthropogenic soil, medium sand, and sandy gravel, map the real diaphragm wall surface. The surface roughness parameters in different soil layers were compared with the reference surface obtained by cast against steel formwork. The following parameters: Sa, Sdr, and Vmc are indicated as being the most useful in numerical description of the concrete surface type and in allowing the determination of the soil surface friction. The novelty of this study is the estimation of the parameter δ (friction angle between the retaining wall surface and the soil), which is, among others, a function of the wall surface roughness. The influence of the type of surface on earth pressure are generally recognized in laboratory tests. Based on the estimated in situ values of δ, the more reliable active and passive pressure coefficients Ka, Kp were calculated for the tested soil layers. The conducted study has a practical significance for designing of retaining construction and makes progress in determination of surface roughness required in Eurocode 7.